Optimisation du procédé de pliage pour la mise en forme de pièces de sécurité automobile - Bahloul, Riadh; Mkaddem, Ali; Santo, Philippe Dal; Potiron, Alain; Saïdane, Delphine (European Journal of Computational Mechanics, 2008)
In this work, the process optimisation of security parts manufacturing is simulated by a finite element modelling including a material damage formulation. Objective functions, stress and damage values occurring in the part at the end of a bending operation, are analysed by means of numerical Design of Experiments and Response Surface Methodology. The process optimisation is carried out by global minimisation and by means of Evolution Strategies. A multi-objective optimisation is carried out in order to identify the best choice of material and process parameters giving a reliable part-life.